Preparation of Future Specialists for Professional Activity on the Basis of National Values - Kosse Rulen Bekirovich (International Journal on Human-Computing Studies, 2021)
This article highlights the issues of the formation of a system of values in the preparation of future junior teachers for professional and spiritual activities, related to the principles of including its content in the curriculum. The role of blocks of general professional disciplines in preparing young teachers for professional activity by organizing the educational process based on national values is emphasized